2020
DOI: 10.1093/mnras/staa756
|View full text |Cite
|
Sign up to set email alerts
|

Modelling double neutron stars: radio and gravitational waves

Abstract: We have implemented prescriptions for modelling pulsars in the rapid binary population synthesis code COMPAS. We perform a detailed analysis of the double neutron star (DNS) population, accounting for radio survey selection effects. The surface magnetic field decay timescale (≈1000 Myr) and mass scale (≈0.02 M ) are the dominant uncertainties in our model. Mass accretion during common envelope evolution plays a non-trivial role in recycling pulsars. We find a best-fit model that is in broad agreement with the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
79
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(80 citation statements)
references
References 176 publications
(235 reference statements)
1
79
0
Order By: Relevance
“…Recent rapid population synthesis studies of double neutron star (DNS) populations have been partially motivated by the development of gravitational wave (GW) astronomy. Software tools such as (Belczynski et al 2018; Chruslinska et al 2017, 2018; Dominik et al 2012), MOBSE (Giacobbo & Mapelli 2018, 2019a,b, 2020), ComBinE (Kruckow et al 2018), and Compact Object Mergers: Population Astrophysics and Statistics (COMPAS) (Chattopadhyay et al 2020; Vigna-Gómez et al 2018) have been used to explore synthetic DNS populations in detail. Most of those studies focus on predicting or matching the observed DNS merger rate, either by investigating different parameterisations of the physics or varying the parameters within the models.…”
Section: Introductionmentioning
confidence: 99%
“…Recent rapid population synthesis studies of double neutron star (DNS) populations have been partially motivated by the development of gravitational wave (GW) astronomy. Software tools such as (Belczynski et al 2018; Chruslinska et al 2017, 2018; Dominik et al 2012), MOBSE (Giacobbo & Mapelli 2018, 2019a,b, 2020), ComBinE (Kruckow et al 2018), and Compact Object Mergers: Population Astrophysics and Statistics (COMPAS) (Chattopadhyay et al 2020; Vigna-Gómez et al 2018) have been used to explore synthetic DNS populations in detail. Most of those studies focus on predicting or matching the observed DNS merger rate, either by investigating different parameterisations of the physics or varying the parameters within the models.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Galaudage et al (2021) suggest that the rapid merger of high-mass systems reduces their radio visibility, which could explain the relative lack of such systems seen in our Galaxy. More generally, the properties of the observed Galactic population are affected by radio selection effects (Chattopadhyay et al 2020), which we do not explore in this work. It may be possible to reconcile the two observed populations by building additional parameters such as the spins or the orbital period into the model (Kruckow 2020).…”
Section: Resultsmentioning
confidence: 96%
“…The probability of this happening by chance (ignoring any selection effects, cf. Chattopadhyay et al 2020) is only 0.2%. One possible correction is that binary evolution changes the compactness of the core, leading to a reduced remnant mass relative to single stars with the same carbon-oxygen core mass for which the Mandel & Müller (2020) model was calibrated.…”
Section: Double Neutron Starsmentioning
confidence: 91%